Flow Mediated Dilation in Systemic Sclerosis: Association with clinical findings, capillaroscopic patterns and endothelial circulating markers - Corrado, Addolorata; Mansueto, Natalia; Correale, Michele; Rella, Valeria; Tricarico, Lucia; Altomare, Alberto; Brunetti, Natale Daniele; Cantatore, Francesco Paolo; Rotondo, Cinzia (Vascular pharmacology, 2024)
Endothelial dysfunction represents a key feature of the pathological process underlying micro and macro-vascular damage in Systemic Sclerosis (SSc). This study aims to improve knowledge of the physiopathology of vascular damage in SSc through the assessment of the endothelial dysfunction by Flow Mediated Dilation (FMD) and serum levels of circulating endothelial dysfunction markers and the correlation of macrovascular damage with clinical findings and microvascular capillaroscopic patterns. 57 SSc patients and 37 healthy subjects were recruited. All included subjects underwent radial artery FMD test and Nailfold Video-Capillaroscopy; serum levels of Vascular Endothelial Growth Factor (VEGF), Vascular Cell Adhesion Molecule-1 (VCAM-1) and angiopoietin-2 were evaluated. Compared to healthy subjects, in SSc patients lower FMD and higher time needed to obtain the maximal FMD responsewere observed, whereas serum levels of VEGF, VCAM-1, and angiopoietin-2 were significantly higher. The impairment of FMD values was associated with disease duration, pulmonary arterial hypertension, and digital ulcers and correlates with greater microvascular damage evaluated by Nailfold Video-Capillaroscopy… An inverse relationship between VEGF, angiopoietin-2, VCAM-1 levels and FMD was observed, but only VEGF and angiopoietin-2 were significantly higher in patients with digital ulcers and pulmonary arterial hypertension. FMD ultrasound test and circulating levels of endothelial dysfuncion markers could be useful as biomarkers of vasculopathy and could be a helpful tool in the overall assessment of vascular injury in Systemic Sclerosis patients. [Display omitted]